Tobacco smoking policies in Australian alcohol and other drug treatment services, agreement between staff awareness and the written policy document - Eliza Skelton; Billie Bonevski; Flora Tzelepis; Anthony Shakeshaft; Ashleigh Guillaumier; Adrian Dunlop; Sam McCrabb; Kerrin Palazzi (BMC, 2017)
Abstract Background Comprehensive smoke-free policy in the alcohol and other drug (AOD) setting provides an opportunity to reduce tobacco related harms among clients and staff. This study aimed to examine within AOD services: staff awareness of their service's smoking policy compared to the written policy document and staff and service factors associated with accurate awareness of a total ban and perceived enforcement of a total ban. Methods An audit of written tobacco smoking policy documents and an online cross-sectional survey of staff from 31 Australian AOD services. In addition, a contact at each service was interviewed to gather service-related data. Results Overall, 506 staff participated in the survey (response rate: 57%). Nearly half (46%) perceived their service had a total ban with 54% indicating that this policy was always enforced. Over one-third (37%) reported a partial ban with 48% indicating that this policy was always enforced. The audit of written policies revealed that 19 (61%) services had total bans, 11 (36%) had partial bans and 1 (3%) did not have a written smoking policy. Agreement between staff policy awareness and their service's written policy was moderate (Kappa 0.48) for a total ban and fair (Kappa 0.38) for a partial ban. Age (1 year increase) of staff was associated with higher odds of correctly identifying a total ban at their service. Conclusions Tobacco smoking within Australian AOD services is mostly regulated by a written policy document. Staff policy awareness was modest and perceived policy enforcement was poor.